2019
DOI: 10.1177/0886260519852629
|View full text |Cite
|
Sign up to set email alerts
|

Counterfactual Thinking Among Victims of Sexual Assault: Relationships With Posttraumatic Stress and Posttraumatic Growth

Abstract: Counterfactual thinking is thinking of alternatives to events that have already occurred. The purpose of this quantitative study was to investigate the relationships between counterfactual thinking and both posttraumatic stress and posttraumatic growth among undergraduate women who identified as having been sexually assaulted ( N = 199). Participants who identified as sexual assault victims completed measures of posttraumatic stress, posttraumatic growth, and counterfactual thinking online. Upward counterfactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The sample sizes of studies ranged from 2 to 39,703 with 19 (48.8%) studies having used qualitative, 19 (46.3%) quantitative, and 3 (7.3%) mixed-methods. The vast majority (63.4%) of studies were conducted in the USA (Cole and Lynn, 2010;Singh et al, 2010;Drauker et al, 2011;Warner Stidham et al, 2012;Williams and Nelson-Gardell, 2012;Wilson et al, 2012;Arias and Johnson, 2013;Davidson et al, 2013;McClain and Frederick Amar, 2013;Foster and Hagedorn, 2014;Ullman, 2014;Bryant-Davis et al, 2015;Kelley and Gidycz, 2015;Simon et al, 2015;Crews et al, 2016;Hartley et al, 2016;Hitter et al, 2017;Kerlin and Sosin, 2017;Smigelsky et al, 2017;Barnett and Maciel, 2019;Catabay et al, 2019;Kirkner and Ullman, 2019;Lahav et al, 2019;Nelson et al, 2019;Saint Arnault and Sinko, 2019;Strauss Swanson and Szymanski, 2020) followed by European studies with 9.8% (Phanichrat and Townshend, 2010;Whitelock et al, 2013;Perez-Gonzalez et al, 2017;Anderson et al, 2019), and two in South Africa (Phasha, 2010;Walker-Williams et al, 2012). One study each was from Australia (Vilencia et al, 2013), Bangladesh (Kaiser and Sinanan, 2020), Brazil (Pessoa et al, 2017), India (George and Bance, 2019), Israel (Kaye-Tzadok and Davidson-Ard, 2016),...…”
Section: Findings General Study Characteristicsmentioning
confidence: 99%
“…The sample sizes of studies ranged from 2 to 39,703 with 19 (48.8%) studies having used qualitative, 19 (46.3%) quantitative, and 3 (7.3%) mixed-methods. The vast majority (63.4%) of studies were conducted in the USA (Cole and Lynn, 2010;Singh et al, 2010;Drauker et al, 2011;Warner Stidham et al, 2012;Williams and Nelson-Gardell, 2012;Wilson et al, 2012;Arias and Johnson, 2013;Davidson et al, 2013;McClain and Frederick Amar, 2013;Foster and Hagedorn, 2014;Ullman, 2014;Bryant-Davis et al, 2015;Kelley and Gidycz, 2015;Simon et al, 2015;Crews et al, 2016;Hartley et al, 2016;Hitter et al, 2017;Kerlin and Sosin, 2017;Smigelsky et al, 2017;Barnett and Maciel, 2019;Catabay et al, 2019;Kirkner and Ullman, 2019;Lahav et al, 2019;Nelson et al, 2019;Saint Arnault and Sinko, 2019;Strauss Swanson and Szymanski, 2020) followed by European studies with 9.8% (Phanichrat and Townshend, 2010;Whitelock et al, 2013;Perez-Gonzalez et al, 2017;Anderson et al, 2019), and two in South Africa (Phasha, 2010;Walker-Williams et al, 2012). One study each was from Australia (Vilencia et al, 2013), Bangladesh (Kaiser and Sinanan, 2020), Brazil (Pessoa et al, 2017), India (George and Bance, 2019), Israel (Kaye-Tzadok and Davidson-Ard, 2016),...…”
Section: Findings General Study Characteristicsmentioning
confidence: 99%
“…Barnett and Maciel 84 In this study of undergraduate women who have experienced sexual assault, both upward counterfactual thinking (i.e. thinking of preferable alternative outcomes) and downward counterfactual thinking (i.e.…”
Section: Study Type 3: Quantitative Non-randomised Studymentioning
confidence: 95%
“…provided evidence that sexual assault/abuse may be associated with an increased risk of mental illness diagnosis/symptoms in adulthood. The most common mental illness identified in these studies was PTSD (n=14) 6,26,27,31,37,[83][84][85][86][87][88][89][90][91] , followed by depression (n=9) 26,27,31,85,86,90,[92][93][94] , suicidality or NSSI (n=6) 7,62,73,74,86,93 and anxiety (n=4). 83,85,86,93 Some of these studies also identified psychosis (n=2) 93,95 , eating disorders (n=2) 85,86 , bipolar disorder (n=2) 85,86 , neurotic disorders (n=1) 93 , and psychiatric disorders generally (n=1).…”
Section: Priority Population Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have used these scales, especially the PTGI-21, as well as other adapted scales specific to the given study, to analyze PTG among those who have experienced sexual assault (Barnett & Maciel, 2019;Cole & Lynn, 2010;Frazier et al, 2001;Grubaugh & Resick, 2007;Hassija & Turchik, 2016;Ullman, 2014). Several of these researchers specifically focused on the relationship between PTG and PTSD and found mixed results (Barnett & Maciel, 2019;Cole & Lynn, 2010;Grubaugh & Resick, 2007). However, the majority of these findings show some degree of growth for study participants, even as soon as two weeks after the trauma (Frazier et al, 2001).…”
Section: Scales and Measurementsmentioning
confidence: 99%